Knowledge, Attitudes, and Practices of Intensive Care Unit Nurses Regarding Oral Care for Intubated Patients in Hebron Hospitals, Palestine - Nesreen Alqaissi; Mohammed Qtait (SAGE Open Nursing)
Introduction Oral care in intubated patients is essential to prevent ventilator-associated pneumonia and other complications. Intensive care unit (ICU) nurses play a vital role in implementing oral care protocols effectively for intubated patients. Objective This study aimed to assess the knowledge, attitudes, and practices (KAP) of ICU nurses in Hebron hospitals, Palestine, regarding oral care for intubated patients. Methods A cross-sectional survey was conducted among 108 ICU nurses using a structured questionnaire that covered demographic data, KAP. Results Of the participants, 43.45% demonstrated good knowledge, while 56.55% had poor knowledge. Positive attitudes were reported by 77.5% of the nurses, and good practices were observed in 46.5% of them. No significant correlation was found between demographic variables and KAP ( p > 0.05). However, a statistically significant positive correlation was found between knowledge and practice ( r = 0.474, p  < 0.001). Conclusion Although most ICU nurses exhibited positive attitudes toward oral care, substantial gaps were identified in their knowledge and clinical practice. These findings highlight the need for continuous education and the implementation of standardized oral care protocols to enhance the quality of care in ICUs.